Advanced kidney cancer: treating the elderly. Issue 12 (December 2013) - Zustovich, Fable; Novara, Giacomo
Advancing age represents the primary risk factor for renal tumors. Despite findings on the inhibition of angiogenesis that have led to six new drugs to treat metastatic renal cell carcinoma, elderly patients have not been fully represented in clinical trials. In addition, current opinions regarding nephrectomy in elderly patients are conflicting. Available data refer to the efficacy and safety of sorafenib, sunitinib, everolimus, bevacizumab and temsirolimus in patients aged 65 years and older; safety and efficacy data are available only for sunitinib, sorafenib, and everolimus in patients aged 70 years and older and only sorafenib has safety data for patients aged 75 years and older. A different approach based on evaluating comorbidities at baseline, risk of drug interactions and the impact of antitumor treatment in patients with polytherapy regimen is discussed. A decision-making algorithm is proposed to facilitate the selection of the best therapy for kidney tumors for a specific elderly patient profile.